The strategic role of principal management in enhancing teacher performance within rural madrasah settings - Alya Mahirotun Numa; Ifada Novikasari (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Teacher performance is a vital element in achieving educational quality, particularly within Islamic-based schools located in rural areas. The role of the principal's management is believed to be a strategic factor influencing the effectiveness of teacher performance; however, it has not been extensively examined quantitatively in the context of Islamic elementary schools in rural settings. Methods: This study employed a quantitative associative approach using a field survey method involving 23 teachers at MI Ma’arif NU 01 Dawuhan Wetan. Data collection techniques included observation, documentation, and questionnaires that were validated and tested for reliability. Data analysis was conducted using simple linear regression with SPSS to determine the significant influence of the principal's management (variable X) on teacher performance (variable Y). Findings: The analysis revealed that the principal's management has a positive and significant influence on teacher performance, with an R² value of 0.810, indicating that the principal's management can explain 81% of the variation in teacher performance. The significance value (Sig.) of 0.000 and the t-value of 9.452, which is greater than the t-table value (1.724), further support this conclusion. Conclusion: The principal’s management has been proven to be a determining factor in improving teacher performance at MI Ma’arif NU 01 Dawuhan Wetan. The quality of planning, supervision, and leadership directly contributes to enhancing teachers' professionalism, responsibility, and productivity. Novelty/Originality of this article: This study provides empirical contributions to the field of Islamic education management by presenting quantitative evidence on the importance of school leadership in the context of madrasahs in rural areas. The findings may serve as a reference for developing management-based policies to improve the quality of education in Islamic elementary schools and similar institutions.